Idārah Ta’allum al-Lughah al-‘Ārabiyah fī Ma’had Rauḍah al-Jannah al-Islāmiy Malang: Istinādan ilā Azzakāāt al-Muta’addidah Howard Gardner - Mufliha Mufliha; Syuhadak Syuhadak; Muassomah Muassomah (Universitas Yudharta Pasuruan, 2022)
This research aims to find out and describe in detail about management of arabic language learning in Roudhotul Jannah Islamic Boarding School based on multiple intelligence Howard Gardner perspective. While this type of research is a case study because the researchers analyze and describe in detail about an institution. This study uses type of case study because the researchers emphasize a fact related to the management of multiple intelligence-based on learning in Howard Gardner perspective. The data collection techniques in this study are observation, interview and documentation. Daily activities include linguistic activities and deposit activities including in language intelligence or linguistic intelligence. Arabic language learning at the Roudhotul Jannah Islamic Boarding School includes four language skills, namely reading, writing, listening and speaking. Speaking skills are included in several intelligences, including linguistic intelligence, logical intelligence, and physical intelligence. Writing skills are included in carnal intelligence and linguistic intelligence. Meanwhile, listening skills are included in lingguistic intelligence, musical intelligence and interpersonal intelligence.